Animistic Practices in the Production of Indigenous Visual Arts in the Bussie Traditional Area, Ghana - Kombui, Babaaradio; Asante, Eric Appau; Adom, Dickson; Padditey, Eugene (Graduate School of Institut Seni Indonesia Yogyakarta, 2024)
The concept of the supreme deity delegating power to lesser spirits and quasi-mythological deities has been part of the esteemed worldview of the Sissala ethnic society. As such, animistic practices and strict observance of taboo systems permeate in the production of indigenous visual artefacts that served as receptacles and offerings for the deities and spirits believed to rule the cosmos and human affairs among the Sissala of the Bussie traditional area. The indigenous arts were practiced by specialized village guilds and the skills are passed on to the younger generation through hereditary and apprenticeship. This phenomenological study rooted in the qualitative research was conducted within one year from June 2021 to August 2022. Data were garnered via interviews, focus group discussions, and observations from 30 study participants who were selected via purposive and snowballing sampling designs, consisting of 18 master-artists, and 12 non-craft professionals. The study revealed the remarkable history and animistic practices in the acquisition of materials and preparation of tools and equipment for the production of the indigenous visual arts. The study contends that the indigenous arts of the Sissala ethnic society are culture-specific and are inseparable from worldviews of the people. Praktik Animistik dalam Produksi Seni Visual Asli di Area Tradisional Bussie, Ghana AbstrakKonsep tentang dewa tertinggi yang mendelegasikan kekuasaan kepada roh-roh yang lebih rendah dan dewa-dewa semi-mitologis telah menjadi bagian dari pandangan dunia yang dihormati dalam masyarakat etnis Sissala. Oleh karena itu, praktik animisme dan kepatuhan ketat terhadap sistem tabu meresap dalam pembuatan artefak visual tradisional yang berfungsi sebagai wadah dan persembahan untuk dewa-dewa dan roh-roh yang diyakini mengatur kosmos dan urusan manusia di antara masyarakat Sissala di wilayah tradisional Bussie. Seni tradisional ini dipraktikkan oleh kelompok pengrajin desa yang khusus, dan keterampilannya diwariskan kepada generasi muda melalui jalur keturunan dan sistem magang. Studi fenomenologis yang berakar pada penelitian kualitatif ini dilakukan selama satu tahun, dari Juni 2021 hingga Agustus 2022. Data dikumpulkan melalui wawancara, diskusi kelompok terfokus, dan observasi dari 30 partisipan yang dipilih melalui desain sampling purposif dan snowballing. Partisipan terdiri dari 18 seniman ahli dan 12 profesional non-pengrajin. Studi ini mengungkap sejarah yang luar biasa serta praktik animisme dalam pengadaan bahan dan persiapan alat serta peralatan untuk produksi seni visual tradisional. Studi ini menegaskan bahwa seni tradisional masyarakat etnis Sissala bersifat spesifik budaya dan tidak terpisahkan dari pandangan dunia masyarakatnya.